Inhibitory effect of α-cubebenoate on atopic dermatitis-like symptoms by regulating Th2/Th1/Th17 balance in vivo. (12th June 2022) - Lee, Jung-Eun; Choi, Young-Whan; Im, Dong-Soon
Abstract: Ethnopharmacological relevance: Bakumijiogan (Kampo herbal formulation) and Kangqian decoction (Chinese herbal medicine formulation) have been used for the treatment of atopic dermatitis (AD) like symptoms. Schisandra chinensis Baill (Family: Magnoliaceae) is a component of both formulations. Its extracts showed inhibition of AD. Aim of the study: We aimed to elucidate an active phytochemical from Schisandra chinensis and evaluated its effects on AD-like symptoms. Materials and methods: We fractionated a component from Schisandra chinensis by chasing inhibitory activity on mast cell degranulation. We identified α-cubebenoate as an active phytochemical and investigated its effects by using an in vivo 1-chloro-2, 4-dinitrobenzene (CDNB)-induced AD model in BALB/c mice. Results: α-Cubebenoate significantly decreased CDNB-induced skin hypertrophy and accumulation of mast cells in the epidermis and dermis. Increases in pro-inflammatory chemokine and cytokine levels in the skin, lymph node size, and immunoglobulin E levels in the serum were significantly ameliorated by α-cubebenoate. Conclusion: α-Cubebenoate regulates dermal immune responses by suppressing the Th2/Th17/Th1 immune balances, resulting in amelioration of AD-like symptoms and suppression of immune response in lymph nodes. Thereby, this study provides evidence for its therapeutic efficacy in the treatment of AD symptoms. Graphical abstract: Image 1